Switzerland : Selected Issues Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The paper assesses the competitiveness of Swiss exporters, and shows that the effect of nominal exchange rate on trade balance depends on the degree of exchange rate pass-through and on trade elasticities. It highlights that the degree of exchange rate pass-through should also be factored in monetary policy decisions. The authorities are considering legislative changes to strengthen macroprudential oversight by supporting the mutual cooperation between Financial Market Supervisory Authority (FINMA) and Swiss National Bank (SNB) over the financial stability. The scope of the too-big-to-fail (TBTF) proposal should also be broadened to address systematic risk.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet